Phenyl propyl polysiloxane modified epoxy resin IV: flame retardancy and smoke suppression - Wang, Changzeng; Li, Shuxin; Cao, Dongfeng; Ji, Yundong; Xu, Chengxin; Wang, Dongzhi (Polymer degradation and stability, 2025)
•Compared with the epoxy, the modified resins show a 60 % decrease in the total smoke release.•The maximum specific optical density (Ds, max) of three composites, which are reinforced by three different kinds of fibers, all hover around 300.•The mechanism of smoke suppression by silicone is explained in both gas and condensed phases. The toxicity of smoke emitted from epoxy resins (EPs) and their composites in fires presents a substantial risk to human health, highlighting the continuous research efforts aimed at reducing smoke production from EP. This study utilizes phenyl propyl polysiloxane (PPPS) as a modifier to effectively decrease smoke emissions from EPs and their composites. Based on the cone calorimeter test findings, the modified epoxy resins (P/Es) exhibited a reduction of almost 60 % in total smoke emissions. Furthermore, the maximum specific optical density (Ds, max) measurements of glass fiber, carbon fiber, and Kevlar fiber reinforced P/Es in a single-chamber test all demonstrated values under the international standard requirement of 400. Examination of residual char through FTIR, SEM, and XPS techniques indicated that the presence of siloxane interfered the soot nucleation and facilitated the formation of a protective C/O/Si layer upon combustion, leading to decreased volatile emissions. The significance of the pyrolysis protective layer in influencing the thermal properties and smoke emissions of resins has been elucidated. The study suggests that silicon can efficiently capture and stabilize carbon and oxygen, providing important implications for composites research on suppressing smoke and improving post-fire strength.